KONTRIBUSI PENDAPATAN, HAMBATAN AKSES DAN KONTROL PEREMPUAN TERHADAP KEGIATAN EKONOMI DALAM UPAYA MENDUKUNG PENDAPATAN RUMAH TANGGA PETANI DI KABUPATEN LOMBOK BARAT - Ni Luh Sri Supartiningsih (Fakultas Pertanian Universitas Mataram, 2023)
Women currently have an important role in development, besides acting as housewives, they are also the breadwinners for the family. Likewise, the role of women in the farmer's household, apart from these two roles, they also play a role in supporting the activities of various social institutions in their rural environment. Limited access and control of women over economic activities can be the cause of their low contribution to household income. The purpose of this study: (1) to analyze the contribution of women's income to the income of farmer households; (2) Identify access and control barriers faced by women in supporting farm household income. This research was designed in the form of descriptive research, the respondents were determined using the purposive random sampling method on the basis of the consideration that women are the wives of farmers and have productive activities. The research results show; (1) The average contribution of women's income to farmer household income is 48.01%, (2) Barriers to women's access and control to support the household economy include: Skills owned by women are still limited; Stereotyped Attitudes of Women; women's domestic work time outpouring; the involvement of women in empowerment activities that has not been maximized: The relationship between women and men in the household;